The Field Of Equivalent Some Numeral Methods (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2008)
This paper describes some properties of methods for numeral solving partial differential equations. A number of identities are proved to show there are regions of equivalency for finite differences methods and finite elements Ritz-method.